Pengaruh Taste, Packgaging, Price dan Inovation Terhadap Purchase Intention: Studi Kasus Terhadap Minat Beli Teh Desa pada Mahasiswa di Purwokerto - Rangga Rifqi Zachary; Totok Haryanto; Herni Justiana Astuti; Purnadi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The aim of this research is to analyze the factors that influence Taste, Packgaging, Price and Innovation on Teh Desa Purchase Intention among Students in Purwokerto. This type of research is a quantitative method. In data collection techniques, researchers used surveys and distributed questionnaires in Purwokerto. The sampling technique used purposive sampling with a research sample of 153 respondents. The results of this study show that Taste has a positive effect on Teh Desa Purchase Intention among Students in Purwokerto, Packgaging has a positive effect on Teh Desa Purchase Intention among Students in Purwokerto, Price has no effect on Teh Desa Purchase Intention among Students in Purwokerto and Innovation has no effect on Teh Desa Purchase Intention among Students in Purwokerto.